Type A aortic syndromes in COVID‐19 positive patients: Case series from a UK multicentre study. Issue 8 (12th May 2021) - Lopez‐Marco, Ana; Harky, Amer; Malvindi, Pietro G.; Verdichizzo, Danilo; McPherson, Iain; Roman, Marius; Oo, Aung; Ohri, Sunil
Abstract: Objective: The coronavirus disease (COVID‐19) increases the respiratory complications and carries a higher mortality in the immediate postoperative period. The aim of this study was to analyze the outcomes of patients with type A acute aortic syndromes (AAS) diagnosed with COVID‐19 in the perioperative period. Methods: Retrospective analysis of prospectively collected data between March and August 2020 from 20 participating cardiac surgery centers in the United Kingdom. Results: Among 122 patients who underwent emergency surgical repair for type A AAS at the participating centers, 3 patients (2.5%) tested positive for COVID‐19 in the preoperative screeing, and 4 cases turned to be positive in the postoperative period having been operated on an unknown COVID‐19 status. Another patient was diagnosed of COVID‐19 disease based on radiological features. These eight patients had increased postoperative complications, including respiratory failure, longer ventilation times, and Intensive Therapy Unit (ITU) stay and increased mortality when compared with COVID‐19 negative patients. Conclusion: COVID‐19 disease in the perioperative period of type A AAS poses a challenge. Despite the increasing morbidity and mortality associated with the virus, the prognosis of the aortic disease is poorer and emergency surgery should not be contraindicated based on the COVID‐19 diagnosis alone.